2011
DOI: 10.1186/1471-2296-12-6
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, randomised, double-blind, single-dose study assessing the efficacy of AMC/DCBA Warm lozenge or AMC/DCBA Cool lozenge in the relief of acute sore throat

Abstract: BackgroundClinically proven over-the-counter (OTC) treatment options are becoming increasingly important in the self-management of acute sore throat. The aim of this study was to determine the analgesic and sensorial benefits of two different amylmetacresol/2,4-dichlorobenzyl alcohol (AMC/DCBA) throat lozenge formulation variants, AMC/DCBA Warm lozenge and AMC/DCBA Cool lozenge, compared with an unflavoured, non-medicated placebo lozenge in the relief of acute sore throat due to upper respiratory tract infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 12 publications
2
41
0
Order By: Relevance
“…The outcome measures were throat soreness (11-point ordinal scale; 0 = not sore and 10 = very sore), 9 difficulty in swallowing (100 mm visual analogue scale [VAS]), 12 sore throat pain intensity (100 mm VAS), 11 and sore throat relief (7-point sore throat relief scale, 0 = no relief to 6 = complete relief). 9 These were assessed at 1 minute before the first dose (with exception of sore throat relief), at 1 minute after the first dose, at 5-minute intervals up to 15 minutes, then at 15-minute intervals up to 180 minutes and hourly up to 360 minutes after the first dose.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The outcome measures were throat soreness (11-point ordinal scale; 0 = not sore and 10 = very sore), 9 difficulty in swallowing (100 mm visual analogue scale [VAS]), 12 sore throat pain intensity (100 mm VAS), 11 and sore throat relief (7-point sore throat relief scale, 0 = no relief to 6 = complete relief). 9 These were assessed at 1 minute before the first dose (with exception of sore throat relief), at 1 minute after the first dose, at 5-minute intervals up to 15 minutes, then at 15-minute intervals up to 180 minutes and hourly up to 360 minutes after the first dose.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…At a holding potential of −70 mV, the effects of AMC/DCBA are less pronounced in comparison to the effects of AMC/lidocaine. AMC/DCBA is a fixed and effective combination in overthe-counter lozenges for the treatment of acute sore throat (Wade et al 2011;McNally et al 2010). Therefore, we investigated the blocking potency of AMC/DCBA with the hypothesis that addition of DCBA to AMC might increase the local anaesthetic effects of AMC.…”
Section: Discussionmentioning
confidence: 99%
“…A randomised controlled trial on 310 patients showed a significant analgesic effect and improvements in functional impairment scores by use of these pastilles (Wade et al 2011;McNally et al 2010). Recent studies from our group have led to the theory that such pain relief was not merely as a result of an antiseptic action-a possible blocking effect of voltage-gated sodium channels was considered to be a contributing factor and a viable mechanistic pathway (Buchholz et al 2009).…”
mentioning
confidence: 95%
“…: In reviewing placebo‐controlled efficacy trials of lozenges in patients with acute pharyngitis based on a PubMed literature search for “lozenge AND pharyngitis AND randomized controlled trial” (Table 5), we conclude non‐steroidal anti‐inflammatory drugs (NSAIDs) and topical analgesics can provide short‐term pain relief within 1‐2 hours in comparison with placebo. However, these trials frequently did not address complete remission or failed in detecting superiority over placebo over the course of 3‐4 days ‐ often explained by the natural improvement in the disease in a few days 23, 24, 25…”
Section: Discussionmentioning
confidence: 99%